2018
DOI: 10.3390/jof4010025
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Pulmonary Escape and Dissemination by Cryptococcus neoformans

Abstract: Cryptococcus neoformans is a common environmental saprophyte and human fungal pathogen that primarily causes disease in immunocompromised individuals. Similar to many environmentally acquired human fungal pathogens, C. neoformans initiates infection in the lungs. However, the main driver of mortality is invasive cryptococcosis leading to fungal meningitis. After C. neoformans gains a foothold in the lungs, a critical early step in invasion is transversal of the respiratory epithelium. In this review, we summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 137 publications
(234 reference statements)
0
52
0
Order By: Relevance
“…This (acidic environment), however, does not seem to inhibit the growth of these cells, which suggests that C. neoformans is well adapted to low pH [57]. In part, this adaptation to acidic pH is beneficial to cryptococcal cells in that it allows them access to iron [106,107], which is inaccessible at neutral pH due to iron being bound to transferrin [108].…”
Section: Ph Tolerancementioning
confidence: 99%
“…This (acidic environment), however, does not seem to inhibit the growth of these cells, which suggests that C. neoformans is well adapted to low pH [57]. In part, this adaptation to acidic pH is beneficial to cryptococcal cells in that it allows them access to iron [106,107], which is inaccessible at neutral pH due to iron being bound to transferrin [108].…”
Section: Ph Tolerancementioning
confidence: 99%
“…Although a well-balanced regulation of the immune cell network protects from fatal outcomes in pulmonary cryptococcosis, the precise immunological mechanisms that direct the development of protective or detrimental anticryptococcal immunity are not clearly understood. However, numerous studies in mice clearly indicated that the control and clearance of C. neoformans is strongly reliant on prototypic type 1 immune responses, characterized by the production of inflammatory cytokines such as Interleukin (IL)-2, Tumor necrosis factor (TNF), and particularly Interferon (IFN)-γ as well as the activation of classical macrophages [reviewed in (8)]. Conversely, type 2 biased immune responses have been implicated in disease progression and detrimental outcomes (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous studies in mice clearly indicated that the control and clearance of C. neoformans is strongly reliant on prototypic type 1 immune responses, characterized by the production of inflammatory cytokines such as Interleukin (IL)-2, Tumor necrosis factor (TNF), and particularly Interferon (IFN)-γ as well as the activation of classical macrophages [reviewed in (8)]. Conversely, type 2 biased immune responses have been implicated in disease progression and detrimental outcomes (8). At mucosal surfaces, the release of alarmins such as IL-25, IL-33, and thymic stromal lymphopoietin (TSLP) was identified as important early trigger of type 2 immunity, which is defined by production of the cytokines IL-4, IL-5, and IL-13 [reviewed in (9)(10)(11)].…”
Section: Introductionmentioning
confidence: 99%
“…Cryptococcus neoformans is worldwide opportunistic human fungal pathogen causing life-threatening pneumonia and meningitis in immunocompromised and immunocompetent individuals (1, 2). Cryptococcosis occurs when desiccated yeast or spores are inhaled, proliferate in the host lung and further disseminate into the central nervous system (2, 3). In response to the earliest interactions with host lung stimuli , C. neoformans cells undergo an unusual morphogenic switch, changing from small haploid yeast to large polyploid titan cells (49).…”
Section: Introductionmentioning
confidence: 99%